Heat and sweat management by a cycling garment impact thermal sensations during exercise in hot and moist conditions - Scholler, V.; Groslambert, A.; Marcel-Millet, P.; Simonin, V.; Ravier, G.; Grappe, F. (Sports Engineering, 2020)
The aim of this study was to investigate the impact of six cycling garments constituted of different materials, during a constant moderate cycling exercise in a hot and moist environment on (a) thermal sensation, (b) change of thermoregulatory parameters, and (c) sweat absorption. Ten cyclists from an amateur to a professional level (age: 21 ± 4.6 years, height: 180.1 ± 6.7 cm; body mass: 70.9 ± 7.8 kg, body mass index: 21.8 ± 1.6) performed six-twenty min pedaling sessions at 4 on CR 10 Borg scale in a hot and moist environment (environmental temperature = 32.8 ± 0.9 °C and relative humidity = 63.4 ± 8.5%), wearing six garments composed of different materials. Heart rate, power output, and core temperature were measured continuously. Skin temperature in 16 regions of interest was measured with an infrared camera every 5 min. The rating of perceived exertion and the thermal sensations was measured every twomin. The sweat absorbed by the garment during the exercise was also quantified. The absence of differences concerning power output, heart rate, core temperature, and the mean skin temperature between garments suggested that non-physiological parameters could also explain the significant differences of mean thermal sensations observed between garments (p < 0.05). Indeed, the quantity of sweat absorbed by garment was significantly positively correlated to mean thermal sensations during the exercise (p < 0.05), suggesting that a bad sweat evacuation by the garment involves an increase of thermal sensations. Moreover, the significant relation predicting mean thermal sensations with the quantity of sweat absorbed, the evolution of the skin temperature in the low back, and in the abdomen regions between 0 and 20 min indicated that local heat exchanges by garment would impact thermal sensation.